Potential Clindamycin Resistance in Clindamycin-Susceptible, Erythromycin-Resistant Staphylococcus aureus: Report of a Clinical Failure - Levin, Todd P. (American Society for Microbiology, 2005)
The erm gene product confers clindamycin resistance on Staphylococcus aureus. We report a clindamycin clinical failure where resistance developed on therapy in a D-test-positive strain. D tests of 91 clindamycin-susceptible, erythromycin-resistant S. aureus isolates showed that 68% of methicillin-susceptible and 12.3% of methicillin-resistant S. aureus strains were D-test positive.